Institutional perspectives on corporate social responsibility (CSR) in agricultural enterprises amidst social movement debates - Annamaria Hajdu (Universitäts- und Landesbibliothek Sachsen-Anhalt, 2024)
As climate extremes intensify, biodiversity declines, and ecosystems degrade, agriculture faces scrutiny as both a driver and a victim of these crises. Its dependence on fossil fuels and ethical concerns around intensive farming fuel criticism from civil society. Corporate social responsibility (CSR) in agribusiness relies on voluntary frameworks, yet these often overlook key social and environmental issues. Large farming enterprises engage in CSR, but tensions with activist groups persist, as voluntary efforts fail to meet societal expectations. This study examines CSR in large-scale farming across Argentina, Kazakhstan, Russia, and Romania, uncovering individual motivations, activist resistance, and institutional influences. Using interviews, surveys, participant observation, and document analysis, it reveals how weak institutions shape CSR, why conflicts with social movements emerge, and how discourse failure may persist. The research offers pathways for mitigation of conflicts. – – Da Klimaextreme zunehmen, die Biodiversität schwindet und Ökosysteme sich verschlechtern, steht die Landwirtschaft als Treiber und Opfer dieser Krisen unter Kritik. Ihre Abhängigkeit von fossilen Brennstoffen und ethische Bedenken zur intensiven Landwirtschaft befeuern zivilgesellschaftliche Kritik. Die unternehmerische Sozialverantwortung (CSR) in der Landwirtschaft basiert auf freiwilligen Rahmenwerken, die oft soziale und ökologische Probleme übersehen. Großflächige Agrarbetriebe engagieren sich in CSR, doch Spannungen mit Aktivistengruppen bleiben bestehen. Diese Studie untersucht CSR in der Landwirtschaft in Argentinien, Kasachstan, Russland und Rumänien, beleuchtet individuelle Motivationen, Aktivistenwiderstand und institutionelle Einflüsse. Mithilfe von Interviews, Umfragen, teilnehmender Beobachtung und Dokumentenanalyse zeigt sie, wie schwache Institutionen CSR prägen und warum Konflikte mit sozialen Bewegungen fortbestehen. Sie bietet Ansätze zur Minderung von Konflikten.
urn:nbn:de:gbv:3:4-1981185920-1203166
Keywords: 330; agroholdings; corporate social responsibility; grounded theory; institutional pressure; large-scale agriculture; post-Soviet countries; radical social movement